The FOXO1 Transcription Factor Instructs the Germinal Center Dark Zone Program - Dominguez-Sola, David; Kung, Jennifer; Holmes, Antony B.; Wells, Victoria A.; Mo, Tongwei; Basso, Katia; Dalla-Favera, Riccardo (Immunity (Cambridge, Mass.), 2015)
The pathways regulating formation of the germinal center (GC) dark zone (DZ) and light zone (LZ) are unknown. In this study we show that FOXO1 transcription factor expression was restricted to the GC DZ and was required for DZ formation, since its absence in mice led to the loss of DZ gene programs and the formation of LZ-only GCs. FOXO1-negative GC B cells displayed normal somatic hypermutation but defective affinity maturation and class switch recombination. The function of FOXO1 in sustaining the DZ program involved the trans-activation of the chemokine receptor CXCR4, and cooperation with the BCL6 transcription factor in the trans-repression of genes involved in immune activation, DNA repair, and plasma cell differentiation. These results also have implications for the role of FOXO1 in lymphomagenesis because they suggest that constitutive FOXO1 activity might be required for the oncogenic activity of deregulated BCL6 expression. [Display omitted] •FOXO1 expression in the germinal center is restricted to dark zone B cells•FOXO1-null mouse germinal centers lack dark zones and lose architectural polarity•FOXO1 deletion impairs affinity maturation and IgG1 class switch recombination•FOXO1 instructs the dark zone gene program directly and by licensing BCL6 activity The factors that control germinal center polarity and cyclic reentry are unknown. Dalla-Favera and colleagues demonstrate that the transcription factor FOXO1 instructs a gene program that is required for germinal center dark zone development. Mouse germinal centers devoid of FOXO1 expression fail to support affinity maturation and class switch recombination.